Sulūk al-Qāḍī: Muqāranah Bayna Mafhūm al-Māwardī fī Kitāb Adab al-Qāḍī wa Qawā’id Sulūk al-Qaḍa fī Indūnīsiyā - Yayan Sopyan; Syamsudin Syamsudin (Universitas Islam Negeri Jakarta, 2021)
This study compares the Judicial Code of Conduct formulated by the Supreme Court of Indonesia and the classical Islamic jurisprudence using the case of the book of Adab al-Qāḍī by Al-Māwardī. The study uses a comparative legal approach to see how these two concepts discuss the integrity of judges. This study found that the Judicial Code of Conduct in Indonesia comes from Islamic law, which Al-Māwardī also uses. The Judicial Code of Conduct concept in Indonesia is in line with the theory of moral idealism, which views humans as moral beings who serve as guidelines for human attitudes and behavior. This is in line with the idea of the unity of the relationship between law and morality. Not all Code of Judicial Ethics in the book